Efficient quantum of mechanical simulation of diffusion-weighted MRI - Ahmed J. Allami; Hany Akeel Al-Hussaniy; Amjad Ibraim Oraibi; Zuhair Abdulkareem Dawah (Medicine in Novel Technology and Devices)
Modern magnetic resonance imaging (MRI) experiments require simultaneous spin and spatial dynamics treatment. This paper aims to demonstrate the possibility of simulating a large spin system for diffusion-weighted MRI experiments. The numerical simulation of diffusion MRI depends on Bloch-Torrey equations. The latter describe the behavior of spin systems under the influence of magnetic fields and diffusion processes. They are particularly relevant in magnetic resonance imaging (MRI) and nuclear magnetic resonance (NMR) studies. The equations deal with uncoupled (−1/2) spins associated with three-dimensional spatial dynamics represented by diffusion and flow. The proposed method recommends using an unopened Kronecker product for evolution generators to minimize the simulation time and reduce the occupied computer memory. Two and three-dimensional diffusion-weighted magnetic resonance imaging associated with four pairs of coupled spin systems were utilized to achieve the study's goals. Utilizing four pairs of coupled spin systems in MRI simulation enhances accuracy and realism in modeling interactions between spins, leading to improved tissue characterization and diagnostic capabilities. The obtained results were impossible using previous simulation packages. The results of the study demonstrate that the Spinach library can simulate complex spin systems with significant spatial dynamics.